The funeral makers - Pelletier, Cathie (New York : Macmillan, 1986)
It is the summer of 1959, the eldest of three Mckinnon sisters, descendant of Mattagash's founding fathers, is on her death bed
Maine author.
Keywords: Mattagash (Me. : Imaginary place) -- Fiction; Maine -- Fiction; Aroostook County (Me.) -- Fiction; Mock-heroic literature